PENERAPAN MANAJEMEN KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU PADA MASA COVID 19 DI SMA NEGERI 1 PUJER BONDOWOSO: SMA NEGERI 1 PUJER BONDOWOSO - RUDI SISWO (Mitra Pendidikan, 2022)
The objectives of this research are 1). To find out the principal's management program in improving teacher performance during Covid 19 learning at SMA Negeri 1 Pujer 2). To find out the application of principal management in improving teacher performance during Covid 19 at SMA Negeri 1 Pujer 3). To find out the results and evaluations faced by teachers during the learning process on Covid 19 at SMA Negeri 1 Pujer. This type of research is a qualitative research that describes as well as examines the real condition of the object of research based on the data concluded. Thus, this study seeks to collect objective data or information in the field regarding the application of teacher performance management during the covid 19 period at SMA Negeri 1 Pujer. Meanwhile, the approach used in this research is through a pedagogical and educative approach. The pedagogic approach is used to determine the principal's ability to improve teacher performance, while the educative approach is the approach taken by teachers to students both online and offline. This research was carried out at SMA Negeri 1 Pujer which is located at Raya Bondowoso No. 01 Pujer, Kejayan, Pujer District, Bondowoso Regency for 3 months, from September to November 2021. The subjects of the study were teachers of SMA Negeri 1 Pujer in the 2020/2021 academic year, totaling 25 people as objects and subjects in school action research. Data collection techniques used in this study are 1) Observation Techniques 2) Interview Techniques 3) Documentation Techniques. Data Analysis Techniques, Based on the components in data analysis, in this study data analysis was carried out including 1). Data Collection (data collection and 2). Data Reduction In the problems obtained from this research, the researchers can conclude 1) Principal Management Program In Improving Teacher Performance During the Covid 19 Period, the next program is carried out by the school to provide convenience to students who do not have technological equipment such as android phones or networks. This program is carried out during the Pandami period so that the learning process continues to run well 2). Implementation of Principal Management in Improving teacher performance During Covid 19, the management process carried out by school principals went through several stages as follows: a) implementation. b) planning and c) monitoring. Implementation From the results of the research that the program carried out by the principal, especially the management of the principal, is related to the implementation of the covid 19 learning, the principal makes a learning program both online and offline 3). Results and evaluations faced by teachers during the learning process In Covid 19, results and evaluations faced by teachers during the learning process during covid 19, the principal gave an assessment to teachers by looking at pedagogy, personality, social and professional.